RAPID ANALYSIS OF CAFFEINE AND PARACETAMOL USING MICRO-LIQUID CHROMATOGRAPHY WITH MIXED MODE MONOLITHIC COLUMN - Kesara Ar-sanork (2022)
This work developed a simple and rapid micro-liquid chromatographic method using a synthesized monolithic capillary column for analysis of caffeine and paracetamol in pharmaceutical drugs. The monolithic column was synthesized from methacrylic acid and ethylene dimethacrylate monomers. Due to the anionic and hydrophobic properties of the polymeric stationary phase, complete separation of the two compounds was achieved by addition of Methylamine into the acetonitrile-aqueous buffer (pH 10.0) mobile phase using a micro-liquid chromatograph with uv-visible detector. Under the optimal condition, the two compounds were separated in less than 3 min. Good linearity in the concentration range of 1–50 mg/L (r2>0.997) with detection limits of 0.05 mg/L for paracetamol and 0.30 mg/L for caffeine were obtained. The method was successfully applied to the determination of caffeine and paracetamol in drug samples with percent recoveries of 102 and 99, respectively.